2007
DOI: 10.1007/s00419-007-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of longitudinal elastic waves in composites with a random set of spherical inclusions (effective field approach)

Abstract: The work is devoted to the problem of plane monochromatic longitudinal wave propagation through a homogeneous elastic medium with a random set of spherical inclusions. The effective field method and quasicrystalline approximation are used for the calculation of the phase velocity and attenuation factor of the mean (coherent) wave field in the composite. The hypotheses of the method reduce the diffraction problem for many inclusions to a diffraction problem for one inclusion and, finally, allow for the derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For the case of randomly distributed elastic spheres in elastic media, explicit models, in which effective wavenumber is given by an explicit formula, 42 and self-consistent models, in which it is the solution of a characteristic equation, 40 have been proposed. In the following, the explicit model derived in Ref.…”
Section: A Theorymentioning
confidence: 99%
“…For the case of randomly distributed elastic spheres in elastic media, explicit models, in which effective wavenumber is given by an explicit formula, 42 and self-consistent models, in which it is the solution of a characteristic equation, 40 have been proposed. In the following, the explicit model derived in Ref.…”
Section: A Theorymentioning
confidence: 99%
“…He showed that, for dense composites, the model performed better than the mean-field methods. In addition, Kanaun and Levin (2007) used the effective field and medium approaches to derive the equations describing elastic wave scattering through such composites. Rahimzadeh and Daneshjoo (2014) conducted a comparative study on four different theoretical models for the prediction of propagation behavior of the elastic P-wave in composites reinforced by randomly distributed inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…However, most existing analytical works are either limited to 1D illustrative models or involved in rather lengthy mathematical formulations and numerical calculations, and many of them are even largely focused on periodic metaelastic composites (such as ''metaconcretes'' filled with periodically aligned coated stiff spheres [10,[12][13][14]). Indeed, random metaelastic composites filled with randomly distributed local resonators have received much less attention [15][16][17][18]. Therefore, it is of great interest to develop simple analytical models that can be used to analyze general metaelastic dynamic problems of random composites filled with coated stiff spheres.…”
Section: Introductionmentioning
confidence: 99%